Coronary Artery Disease (Cardiovascular Medicine, 2015)
Coronary Artery Disease offers today's most up-to-date, user-friendly guidance on the evaluation, diagnosis, and medical and surgical treatment of this most important aspect of cardiovascular disease. The book provides comprehensive coverage of every aspect of coronary arterial medicine from cardiac signs and symptoms through imaging and the genetic basis for coronary disease to surgery, interventions, treatment and also to preventive cardiology. The Editors - and a group of contributing world authorities - offer their decades of scientific and clinical experience. The reader will have all the guidance to diagnose and manage a full range of conditions in a series of textbook resources